Initial experiences of recover-e CMH mobile teams in N. Macedonia/patients homes as a therapeutic setting - Bajraktarov, Stojan; Naumovska, Andromahi; Kalpak, George; Milutinovikj, Milosh; Novotni, Ljubusha; Novotni, A (CAMBRIDGE UNIVERSITY PRESS, 2022)
Introduction: RECOVER-e's main purpose is to ensure wellfunctioning community mental health teams in five countries in Europe, one of which is N. Macedonia. The project supports the development and implementation of a multidisciplinary community mental health team - CMH, consisting of a psychiatrist, psychologist, social worker, nurse, and peer worker, delivering evidence-based mental health care to the patient location. This service delivery model was not available in N. Macedonia before the RECOVER-E program. Objectives: Our team set out to design, implement and evaluate recovery-oriented care for people with severe mental illness. We aim to develop evidence-based care pathways and treatment protocols and transition to scale for regional and national decisionmakers, for continued implementation after the project's life span. Methods: All included patients were assessed by a comprehensive questionnaire. The CMH teams meet up on a weekly basis to exchange experiences, discuss different strategies and interventions used. Results: So far, 110 patients underwent baseline assessment, with prospective randomization selected either in treatment or control group. Furthermore, 69 home visits were completed in a time span of 6 months. The patients in the treatment group were visited by the CMH team, making interventions on the spot and devising a treatment strategy for follow-up visits. Conclusions: The intervention is focused on changing mental health care systems to be able to provide community-based mental health care for people with severe mental illness, providing integrated services to people with severe mental illness in order to structurally attain their recovery goals, as well as timely and appropriate care in the event of a crisis.